2015
DOI: 10.1027/1618-3169/a000295
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Serial Auditory Presentation

Abstract: The Rapid Serial Visual Presentation procedure is a method widely used in visual perception research. In this paper we propose an adaptation of this method which can be used with auditory material and enables assessment of statistical learning in speech segmentation. Adult participants were exposed to an artificial speech stream composed of statistically defined trisyllabic nonsense words. They were subsequently instructed to perform a detection task in a Rapid Serial Auditory Presentation (RSAP) stream in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 29 publications
7
38
1
Order By: Relevance
“…In contrast to the RT pattern we observed, both these studies found a graded RT effect as a function of syllable position. In addition, a recent auditory statistical learning study using syllable triplets in which the second and third syllables were deterministically predicted by the first syllable found the same pattern of results: RTs were slowest to target syllables occurring in the first position, intermediate to syllables occurring in the second position, and fastest to syllables occurring in the final position (Franco et al 2015). Taken together, these results suggest that significant RT differences may emerge only when an item can be uniquely predicted from the preceding context.…”
Section: Reaction-time Taskmentioning
confidence: 60%
See 2 more Smart Citations
“…In contrast to the RT pattern we observed, both these studies found a graded RT effect as a function of syllable position. In addition, a recent auditory statistical learning study using syllable triplets in which the second and third syllables were deterministically predicted by the first syllable found the same pattern of results: RTs were slowest to target syllables occurring in the first position, intermediate to syllables occurring in the second position, and fastest to syllables occurring in the final position (Franco et al 2015). Taken together, these results suggest that significant RT differences may emerge only when an item can be uniquely predicted from the preceding context.…”
Section: Reaction-time Taskmentioning
confidence: 60%
“…The function of statistical learning was then assessed using an online, speeded, performance-based measure. Known as the target-detection task, this task was originally used in visual statistical learning studies (Turk-Browne et al 2005;Kim et al 2009) and more recently has been adapted to assess statistical learning in the auditory domain (Batterink et al 2015;Franco et al 2015). The task requires participants to respond to target syllables occurring in a continuous syllable stream and provides an indirect measure of statistical learning (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of words in the structured stream was assessed directly using a rating task, in which participants provided familiarity ratings to words from the stream and foil items made up of recombined syllables. Statistical learning was also assessed indirectly using a target detection task, an online, speeded, performance-based measure (Batterink et al, 2015a, 2015b, Franco et al, 2015). This task requires participants to respond to target syllables occurring in a continuous syllable stream and assesses the extent to which learners use their acquired statistical knowledge to optimize online processing.…”
Section: Introductionmentioning
confidence: 99%
“…This task requires participants to respond to target syllables occurring in a continuous syllable stream and assesses the extent to which learners use their acquired statistical knowledge to optimize online processing. We expected to observe faster reaction times (RTs) to relatively predictable targets (i.e., those occurring in later syllable positions compared to the first position), indexing more efficient processing (e.g., Turk-Browne et al 2005; Kim et al 2009; Batterink et al 2015a, 2015b; Franco et al 2015). Whereas the rating task is presumably most sensitive to explicit memory, the target detection task has the potential to capture knowledge above and beyond what is reflected by explicit memory and may partially reflect contributions from implicit memory (Batterink et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%